Koherensi dan Kejelasan Kalimat dalam Surat Perjanjian Kerjasama: Pendekatan Linguistik dan Legal - Septiani, Sasi; Ramadhany, Chusnul Lintang; Putri, Synta Aulia; Anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze linguistic aspects in cooperation agreement letters, particularly the use of legal terms, sentence coherence, and emphasis through linguistic elements such as bolding and quotation marks. Data were collected from several cooperation agreements in the health sector and analyzed using a qualitative descriptive approach. The results show that legal terms such as